Absorbable collagen sponges loaded with recombinant bone morphogenetic protein 9 induces greater osteoblast differentiation when compared to bone morphogenetic protein 2. Issue 1 (9th February 2017) - Fujioka‐Kobayashi, Masako; Schaller, Benoit; Saulacic, Nikola; Pippenger, Benjamin E.; Zhang, Yufeng; Miron, Richard J.
Abstract: The use of growth factors for the regeneration of soft and hard tissues has been utilized extensively in dental medicine over the past decade. Recently our group found that recombinant human bone morphogenetic protein 9 (rhBMP9) was more osteopromotive than recombinant human bone morphogenetic protein 2 (rhBMP2) when combined with a deprotenized bovine bone mineral bone grafting material. The aim of the present in vitro study was to evaluate the regenerative potential of an absorbable collagen sponge(ACS) specifically designed for extraction socket healing loaded with rhBMP9 when compared to rhBMP2. The adsorption and release kinetics of rhBMP2 and rhBMP9 were first investigated by enzyme‐linked immunosorbent assay quantification. Then, the cellular effects of stromal cell line (ST2) preosteoblasts were investigated utilizing four groups including rhBMP2 and rhBMP9 at both low(10 ng/ml) and high(100 ng/ml) concentrations loaded onto ACS. Cellular attachment(8 hours) and proliferation(1, 3, and 5 days) as well as osteoblast differentiation were investigated by real‐time polymerase chain reaction (PCR) at 3 and 14 days, alkaline phosphatase (ALP) activity at 7 days, and alizarin red staining at 14 days. ACS fully adsorbed both rhBMP2 and rhBMP9 that were slowly released up to 10 days. Although neither rhBMP2 nor rhBMP9 had any effects on cell attachment or proliferation, pronounced effects were observed on osteoblast differentiation. ALP activity was increased seven‐fold with rhBMP2‐high, whereas a marked 10‐fold and 20‐fold increase was observed with rhBMP9‐low and high loaded to ACS, respectively. Furthermore, mRNA levels of collagen1, ALP, bone sialoprotein, and osteocalcin were all significantly higher for rhBMP9 when compared to control or rhBMP2 groups. Alizarin red staining further confirmed that rhBMP9‐low and high demonstrated marked increases in mineralization potential when compared to rhBMP2‐high. The results demonstrate the marked effect of rhBMP9 on osteoblast differentiation when combined with ACS in comparison to rhBMP2 at doses as much as 10 times lower. Further in vivo studies are necessary to investigate whether the regenerative potential is equally as potent.